The Influence of Instagram Promotion, Word of Mouth, and Service Quality on Purchase Decision - wiwid, Dea Anasthasya; Tapa, I Gede Fery Surya (LPPM STIE KRAKATAU, 2025)
This study aims to examine the influence of Instagram social media promotion, word of mouth (WOM), and service quality on customers' purchasing decisions at Bubba Gump Shrimp Co. Bali. The novelty of this research lies in integrating digital marketing engagement with service quality in the context of a premium restaurant in Bali, which has not been widely explored. A quantitative approach was employed from September to October 2025, targeting all customers of Bubba Gump Shrimp Co. Bali. A random sampling technique selected 120 respondents. Data were collected via Likert-scale questionnaires and analyzed using multiple linear regression with SPSS 25. Instagram social media promotion positively and significantly influenced purchasing decisions (t = 4.116, p = 0.000). Word of mouth showed no significant partial effect (t = 0.512, p = 0.609). Service quality had a significant positive effect (t = 6.832, p = 0.000). Simultaneously, all three factors significantly influenced purchasing decisions (F = 45.119, p = 0.000). Management should enhance service quality, optimize digital marketing through engaging Instagram content, and strengthen online WOM strategies to attract more consumers. This study focused on a single premium restaurant in Bali and used self-reported survey data, which may limit generalizability. The research contributes to understanding the combined effect of digital marketing and service quality on consumer behavior in the restaurant industry, providing practical insights for managers to design integrated marketing strategies.